(untitled) (Archaeologia Adriatica, 2010)
This scientific analysis starts from a valuable acquisition of the Archaeological Museum in Zagreb – a very well preserved early medieval winged spear from the vicinity of Dugo Selo, a town twenty kilometers to the east of Zagreb. The spear purchased for the Archaeological Museum in 2007 is of high quality and almost entirely preserved, with damage only on one side of the lower part of the socket (length 473.4 mm; weight 508 g). The spear is characterized by a broad blade, with a visible but not prominent rib, and the greatest span in the middle of the blade (54.4 mm). On both sides of the blade, more on one and less on the other, there are visible traces of double banded spirally twisted damascening with a rosette pattern of the Rosendamast (Rosetendamast) type. The socket of the spear is short (104.4 mm), with a hexagonal section above and a circular section below (28 mm), with a deep (94 mm) but not particularly wide insertion area (23.4 mm). The holes for the nails are located below the low placed wings or lugs, straight on top, and concavely curved below (span 71.8 mm). The ends of the wings are bent horizontally in the shape of the letter L. Each main side of the socket has a pair of elongated grooved bands (90 x 5.3 mm), while each lateral side above the wings has a pair of short grooved bands joined upwards into a point. The spear was brought to the Archaeological Museum in Zagreb and offered for sale by a resident of Dugo Selo, a small town twenty some kilometers east of Zagreb, who noted that it had been found twenty or more years ago on the northern slopes of the hill of Martin Breg during renovation of a nearby vineyard and the lane in the immediate vicinity, next to which the spear was found and handed over to its later owner (perhaps during widening and gravelling of the lane). Hence the location of the find is not certain, and it can be hypothesized, judging from the very good state of preservation, that the spear was actually an aquatic find, and that it came from a riverbed, sand bank, or gravel pit in the vicinity of Dugo Selo (which is near the Sava River). The spear is a typical early Carolingian product, which according to earlier typological-chronological systems would belong to Petersen type B, Paulsen winged spears of the finished type, and Szemeit type A, and accordingly would belong to the early Carolingian period and be dated to the period around AD 800. More recent archaeological research and knowledge acquired in the past twenty years has led to a different consideration and analysis of objects of this type, and the spear from the Dugo Selo vicinity has been analyzed on the basis of this new knowledge (Solberg, Westphal). The analysis was also extended to cover all of the known examples of winged spears in museums and other collections in Croatia (11+1 ex.) and Bosnia and Herzegovina (8 ex.), which for this occasion were subjected to an analysis of their dimensions and proportions, so that they would finally be compared and interpreted in the framework of the morphological postulates and conclusions previously reached by the German archaeologist-restorer H. Westphal. Analysis has shown the existence of several typological groups whose proposed chronological coordinates differ from those parameters used to the present for the investigation and the interpretation of winged spears in the works of Croatian archaeologists. This metrological approach to the analysis of the Croatian finds has confirmed the existence of examples that belong to the earliest tradition of early Carolingian winged spears and has identified several other spears whose morphological characteristics indicate the first half of the 8th century. The remaining spears mainly belong to two main typological groups (Westphal types II and III), i.e. to the period from the second half of the 8th century to within the second half of the 9th century.